The Income Difference of Credited and Uncredited Cocoa Farming in Central Sulawesi, Indonesia - Fatinsyah, Enrico; Harianto, Harianto; Baga, Lukman Mohammad (Agro Bali : Agricultural Journal, 2025)
Cocoa plantations in Central Sulawesi have experienced a decline in productivity due to many plants starting to age, pest and disease attacks, and minimal application of technology. Limited capital causes these problems to be challenging to solve, so the solution is to take credit loan capital. However, many farmers still need to be convinced to take credit. Therefore, this study aims to analyze the differences in cocoa farming income with and without credit and the factors influencing farmers' decisions to take credit. The data used is secondary data from the 2013 Agricultural Census: 2014 Plantation Household Survey. Descriptive analysis is used to describe the characteristics of cocoa farmers in Central Sulawesi. Quantitative analysis is used for farm income analysis, propensity score matching, and logistic regression. The research found that credit positively influenced the income of cocoa farmers in Central Sulawesi. However, it was insignificant because credit was not entirely used to finance productive farming. Factors influencing cocoa farmers' decision to take credit in Central Sulawesi are participation in extension services, cooperative membership, farmer group membership, farmer education level, and land area.